Cultural background of personality - "Linton, Ralph" (London, 1958)
In February, 1943, Swarthmore College invited me to deliver a series of five lectures on the general subject of the interrelations of Culture, Society and the Individual, these lectures being given under the auspices of the Cooper Foundation. As an alumnus of the institution and one who had few opportunities to revisit it since graduation in 1915, it gave me great pleasure to accept.
Keywords: Psychology